Relationship between gingival clinical parameters and the reactivity of the BANA test in subgingival samples from children. - Zuza, Elizangela Partata; de Salis, Ana Maria Vilela; de Toledo, Benedicto Egbert Corrêa; Mendes, Ary José Dias (My University, 2006)
Gingivitis is the first manifestation of periodontal disease, and is characterized by painless and slow evolution. Early diagnosis and intervention must be done to avoid the possibility of precocious periodontitis during the childhood or teenage years. The enzymatic BANA test (N-benzoyl-DL-arginine-naphthylamide) was used to evaluate subgingival samples from 54 children between 6 and 9 years of age. Plaque index (PI) and gingival index (GI) were assessed according to the criteria recommended by Löe (1967). Subgingival plaque was collected from the region that featured the greatest periodontal alteration, represented by a higher gingival index. Resulting data were grouped individually according to visible and non-visible plaque and bleeding and non-bleeding gingiva. Results showed that there was no statistically significant correlation between the presence of visible plaque and the positivity of the BANA test, nor was there a statistically significant correlation between the presence of bleeding and the positivity of the BANA test in subgingival samples obtained from children. This study concluded that the BANA test is not an ideal diagnostic test to be applied to children.
Keywords: diagnostic agent; n benzoylarginine 2 naphthylamide; chi square distribution; child; enzyme assay; evaluation; female; gingivitis; human; male; periodontics; sensitivity and specificity; tooth plaque; Benzoylarginine-2-Naphthylamide; Chi-Square Distribution; Child; Dental Plaque; Dental Plaque Index; Enzyme Tests; Female; Gingivitis; Humans; Male; Periodontal Index; Sensitivity and Specificity